Special Issue on BIM and Its Integration with Emerging Technologies - Inhan Kim; Jung In Kim (Applied Sciences, 2022)
Building information modeling (BIM) has quickly gained attention in the construction industry due to its promising benefits and has become a key technology affecting all phases of construction projects (i.e., design, construction, and operation)[...]